Visible Light Communication System Employing Space Time Coded Relay Nodes and Imaging Receivers; SAIEE Africa Research Journal Soft Computing; Vol. 111, iss. 2 - Mulundumina Sh.-N. Shimaponda-Nava; Achari Sh. Shamin; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Ling Cheng (2020, 2020)
Title screen